Modified Peanut Shell Micro-Column Solid Phase Extraction for the Determination of Silver in Environmental Water Samples by Flame Atomic Absorption Spectrometry - Yang, J.; Zhang, Y.M.; Chen, F.P.; Zhang, H.X. (Asian Journal of Chemistry, 2011)
Peanut shell was chemically modified with phosphoric acid and sodium diethyldithiocarbamate (DDTC), the obtained powder was used as solid phase extraction adsorbent for the determination of trace amounts of silver in environmental water samples by flame absorption spectrometry (FAAS). The effect of pH, sample flow rate and volume, elution conditions and co-existing ions on the recovery of the analyte was investigated. The results showed that silver could be adsorbed at pH 5 and eluted by 5 mL of 0.5 mol L-1 HNO3. Under the optimized conditions, the adsorption capacity of modified peanut shell was found to be 14 mg g-1 for silver. The detection limit of the proposed method was 1.1 ng mL-1 for silver with an enrichment factor of 16.3. The proposed method has been successfully applied to the determination of trace silver in Yellow river, Liusha river and Jialu river water. The recovery of silver for spiked samples was between 96 and 112 %.